Sistem Informasi Monitoring Kinerja Aparat Desa Kalembu Kaha dengan Pendekatan Pieces (International Forum of Researchers and Lecturers, 2025)
Monitoring is an activity that examines a condition to obtain all necessary information. The outcomes monitoring can act as a guide for formulating strategies. Researchers found that in Kalembu Kaha Village, the monitoring of ongoing activities is still carried out traditionally, where the Kaur must go directly to the field to witness existing activities. Therefore, it is important to develop a monitoring system application so that all activities tracked instantaneously. In addition, this will facilitate effort Village Head to evaluate the progress of projects or activities carried out so that they can be on time. Through this research, was identified application, the Village Head can more easily monitor and supervise activities carried out by village officials. This allows the Village Head to evaluate and take action quickly and efficiently